Experimental deposition of NaCl particles from turbulent flows at gas turbine temperatures - Forsyth, P; McGilvray, M; Gillespie, D (Université de Lille, 2018)
The ingestion and deposition of solid particulates within gas turbine engines has become a very signi€cant concern for both designers and operators in recent times. Frequently aircraft are operated in environments where sand, ash, dust, and salt are present, which can drive damage mechanisms from long term component degradation to in-flght flame-out. Experiments are presented to assess deposition characteristics of sodium chloride (NaCl) at gas turbine secondary air system temperature conditions in horizontal pipe flow. Mono-disperse NaCl particles were generated in the size range 2.0 - 6.5 µm, with gas temperatures 390-480 ◦C, and metal temperatures 355-730 ◦C. Two engine-representative surface roughnesses were assessed. An experimental technique for the measurement of deposited NaCl based on solution conductivity was developed and validated. Experiments were carried out under isothermal and non-isothermal/thermophoretic conditions. An initial experimental campaign was conducted under ambient and isothermal conditions; high temperature isothermal results showed good similarity. Under thermophoretic conditions deposition rates varied by up to several orders of magnitude compared to isothermal rates.